Kerch strait – the major transport artery and a fisching area of the Azov-Black Sea pool - D. Ya. Faschuk; O. A. Petrenko (Юг России: экология, развитие, 2015)
Water-economic projects (1970-1980) of artificial regulation of water exchange through passage in connection with reduction during this period of a river drain to Azov sea and growth of its salinity are analysed. Changes of ecological conditions in passage after formation prowound Tuzla of a gully as a result of a storm (November, 1925) and possible hydroecological consequences modern (October, 2003) attempts of construction in passage from the Russian part of a dam for connection are estimated about Tuzla with peninsula Tamansky.